Newspaper coverage of mental illness in Hong Kong between 2002 and 2012: impact of introduction of a new Chinese name of psychosis. Issue 4 (23rd November 2015) - Chan, Sherry K.W.; Ching, Elaine Y.N.; Lam, Kenneth S.C.; So, Hon‐Cheong; Hui, Christy L.M.; Lee, Edwin H.M.; Chang, Wing C.; Chen, Eric Y.H.
Abstract: Aim: In Hong Kong, 'si‐jue‐shi‐tiao' (思覺失調) was officially adopted as the Chinese translation of psychosis in 2001. The new term covered a broader aspect of psychosis, compared with the original term, 'jing‐shen‐fen‐lie' (精神分裂), which gave a negative stereotype as a 'mental split‐mind disorder'. The current study compared the usage of the two terms, and added evidence to the name changing as anti‐stigma strategy. Methods: The usage and themes of the new Chinese name of psychosis 'si‐jue‐shi‐tiao' was examined in 1217 local newspaper articles in comparison with the traditional Chinese name of schizophrenia 'jing‐shen‐fen‐lie'. Results: Results show that an increase use of 'si‐jue‐shi‐tiao' was found equally across themes, whereas 'jing‐shen‐fen‐lie' was decreasingly used in positive/neutral themes over time. The association of 'jing‐shen‐fen‐lie' with dangerous wordings increased over time, but no change was found with the new name. Conclusions: Our finding adds to literature on effects of changing new name on public stigma.